PENGELOLAAN DANA ZAKAT, INFAQ, DAN SHADAQAH PERSPEKTIF SHARIAH ENTERPRISE THEORY - Sigit Hermawan; Restu Widya Rini (Riset Akuntansi dan Keuangan Indonesia, 2016)
The purpose of this study is to analyze the suitability between reporting information ZIS (Alms, infaq and sadaqah) institutions revealed OPZIS with the concept of Shariah Enterprise Theory. This study uses the method of documentation and interviews to management ZIS (Alms, infaq and sadaqah) is done based on those in item concept Shariah Enterprise Theory by analyzing report on the use ZIS ZIS (Alms, infaq and sadaqah) based on four aspects is god, direct stakeholders, indirect stakeholders and nature. The results of this study indicate that management ZIS (Alms, infaq and sadaqah) in Baznas and Lazismu Sidoarjo there are still deficiencies in conformity with the concept Shariah Enterprise Theory god, direct stakeholders and indirect stakeholders have met with perspective shariah Enterprise Theory but for aspects of nature and the employee has not been done by OPZIS.